IDENTIFICATION OF Klebsiella pneumoniae RESISTANT MUTANTS AGAINST BRL 41897A ANTIBIOTIC USING SOUTHERN BLOT ANALYSIS. - M. Kuswandi (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2002)
Isolation of Klebsiella pneumoniae resistant mutants against BRL 41897A antibiotics using TnphoA has yielded 30 mutants which have been characterized. In order to identify whether the mutants are as a result of the insertion (transposition) of TnphoA, and to count how many copies of TnphoA are inserted in the each mutant chromosome, several chromosomal DNA of the mutants have been cut with restriction enzymes and analised using Southern blot method and DIG conjugation. The results showed that at least one mutant (KSL19) carried one copy of transposon, whereas at least 2 mutants (KSL38 and KSL52, ) have 2 copies. It is obvious that TnphoA mutagenesis provides an efficient method of selecting mutants which are defective in genes controlling expression of the outer membrane and the periplasmic membrane proteins.Key words: Resistant K. pneumoniae mutants- TnphoA mutagenesis – BRL 41897A- Southern Blot.